How do ‘busy’ and ‘overlap’ directors relate to CEO pay structure and incentives? - Pathan, Md Shams Tabrize; Wong, P.H.; Benson, K. (WILEY, 2019)
© 2017 AFAANZ We examine how CEO compensation is affected by the presence of busy and overlap directors. We find that CEOs at firms with more busy directors receive greater total pay, fixed salary and equity-linked pay and exhibit higher pay-performance (delta) and pay-risk (vega) sensitivities. Our results also suggest that CEOs at firms with more overlap directors take smaller total pay and equity-linked pay and reveal lower delta and vega. We further show that the impact of busy and overlap directors on CEO pay is more visible for firms with less complexity and low information acquisition cost.